h) [3(x - 2) = 2(y - 3) 18(y-2) + y = 3(2x + 3)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo a passo:
Anexos:
![](https://pt-static.z-dn.net/files/de2/333e78a20f29621f00ef187dc5a9e5ee.png)
albertrieben:
verifique sua resposta x = 2, y = 3
Respondido por
0
Vamos lá.
sistema
3*(x - 2) = 2*(y - 3)
18*(y - 2) + y = 3*(2x + 3)
simplifique
3x - 6 = 2y - 6
3x = 2y
19y - 36 = 6x + 9
19y - 6x = 45
19y - 4y = 45
15y = 45
y = 3
3x = 6
x = 2
S = (2, 3)
Anexos:
![](https://pt-static.z-dn.net/files/d24/cad2e5dbdd4d64e287b7f0bff234159f.jpg)
Perguntas interessantes
Matemática,
6 meses atrás
Inglês,
6 meses atrás
Matemática,
6 meses atrás
Pedagogia,
6 meses atrás
Artes,
6 meses atrás
Química,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás